Analysis of relationship between gene status (EGFR, ALK, ROS1)and clinicopathological features in 1 232 cases of lung adenocarcinoma with lesion of maximum diameter≤1 cm - ZHU Xia, WANG Xin, JIN Jingjing, XIAO Li (Zhenduanxue lilun yu shijian, 2024)
Objective To study relationship between gene status [epidermal growth factor receptor（EGFR）, anaplastic lymphoma kinase (ALK) and ROS proto-oncogene 1, receptor tyrosine kinase (ROS1)] in cases with pathological lung adenocarcinoma lesion of maximum diameter ≤1 cm. Methods A total of 1 232 patients with lung adenocarcinoma lesion of maximum diameter ≤1 cm were enrolled in the Pathology department of Huadong Hospital from January 2013 to October 2020. For patients with multiple lesions, only the biggest lesion was selected. The gene status of EGFR, ALK and ROS1 were identified and clinicopathological characteristics were retrospectively analyzed. Results There were 387 males and 845 females，with a mean age of 54 years.There were 182 (14.8%) cases of adenocarcinomas in situ, 778 (63.1%) cases of minimal invasive adenocarcinomas, 249(20.2%) invasive non-mucinous adenocarcinomas, and 23 (1.9%) invasive mucinous adenocarcinomas. It revealed that 43.1% (352/817 cases) had EGFR gene mutations, of which 46.9% (165/352 cases) were 21L858R mutations and 40.6% (143/352 cases) were 19Del mutations, and 0.9% (3/352 cases) were 18G719X/20S768I and 21L858R/20S768I double mutations. The rate of EGFR mutation were 31.0% (40/129), 42.0% (208/495), 58.4% (104/178), and 0 (0/15) for adenocarcinoma in situ, minimal invasive adenocarcinoma, invasive non-mucinous adenocarcinoma, and invasive mucinous adenocarcinoma, respectively.And 23.1% (3/13 cases) had different EGFR mutation detected for different lesions in the same patient (In 13 cases with 2 lesions of lung adenocarcinoma successively, 2 cases were positive for 19Del mutation in the first postoperative lesion and EGFR wild-type in the second lesion: one case was EGFR wild type in the first postoperative lesion and 21L858R mutation in the second lesion). The rate of EGFR mutations was correlated with histological type and age, and not associated with sex or smoking. EGFR mutations was more likely to occur in the age group over 60 years and in invasive non-mucinous adenocarcinomas. It showed that 1.9% (22/1168 cases) were positive for ALK rearrangements, with a positive rate of 5.2% in invasive non-mucinous adenocarcinomas and of 2.6% in patients ≤60 years. The positive rate of ALK rearrangement in adenocarcinomas with solid components (22.2%, 4/18) was significantly higher than that in invasive non-mucinous adenocarcinomas (5.2%, 12/233) and adenocarcinomas without solid components (1.1%, 12/1095). It showed that 0.8% (6/795 cases) were positive for ROS1 rearrangements, independent of sex, age, smoking and histological type. A total of 382 cases were tested for EGFR, ALK and ROS1 simultaneously, of which 40.6% (155/382) of the tumours containing one of these three mutations or rearrangements status, and no co-exist in either or all three. Conclusions In this single-center study, minimal invasive adenocarcinomas accounts for the majority (63.1%) of lung adenocarcinomas with a lesion size ≤1 cm. At least 40% of them have mutations or rearrangements in one of the three genes (EGFR, ALK and ROS1)， and none of which were significantly associated with sex or smoking. The most common EGFR mutations are 21L858R and 19Del, which occur more frequently in invasive non-mucinous adenocarcinomas in the >60 age group, while ALK rearrangements occur more frequently in solid-component adenocarcinomas in the ≤60 age group. The incidence of ROS1 rearrangements is low. The molecular change may be different in the same patien to with multiple adenocarcinomas，molecular testing foci is necessary for each lesion.